Assessment of groundwater reservoir and the influence of its characteristics on water dynamic control - Yao, Wenli (Water science and technology : a journal of the International Association on Water Pollution Research, 2023)
Groundwater reservoirs play an important role in regional water volume balance. In order to ensure the efficiency of a groundwater reservoir and obtain its maximum value, it is necessary to figure out its characteristics, such as minimum water level, normal water level, and maximum water level. The characteristics not only determined the storage capacity but also influenced the water allocation and utilization. Therefore, this paper took a groundwater reservoir built in an alluvial fan as an example to assess its storage capacity and the influence on water dynamic control. The alluvial fan was located in the front of Lao River, where there were an alluvial-diluvial fan, groundwater storage space, and natural impervious boundary. Therefore, it was an ideal place for constructing a groundwater reservoir. Through theoretical analysis and numerical simulation, the storage capacity was determined, and the influence of groundwater reservoir characteristics on water dynamic control was analyzed. On this basis, the water-supply method in the research area was confirmed. This paper will present a new method for repairing the groundwater system and protecting the ecological environment